Symposium 2016-2017: globalisation, inequality and the rise of populism globalisation, inequality and populism - Nolan, B (The Statistical and Social Inquiry Society of Ireland, 2017)
Inequality in the distribution of income and wealth among individuals has now come to the fore as a core concern across the industrialised world. In 2013 then President of the United States Barack Obama identified rising income inequality as “the defining challenge of our times”. The Managing Director of the International Monetary Fund Christine Lagarde has stated that “reducing excessive inequality is not just morally and politically correct, but it is good economics.” Secretary-General of the OECD Angel Gurría has emphasized that “Inequality can no longer be treated as an afterthought. We need to focus the debate on how the benefits of growth are distributed”. This reflects the fact that inequality has been rising in many rich countries, and that this is seen as undermining economic growth, ‘squeezing’ middle and lower income households, exacerbating social ‘bads’ such as health inequalities, and undermining social solidarity and trust. Most recently, in light of political developments, it has also been held responsible for fuelling the rise of populism.